Kualitas Sanitasi Higiene dengan Peningkatan Frekuensi Diare pada Balita - Islam, Fahrul; Aisyiah, Nurul; Erwin Ashari, Agus; Ahmad, Haeranah (Universitas Pembangunan Nasional Veteran Jakarta, 2024)
Background: Diarrhea is a leading cause of child mortality. Approximately 90% of diarrhea-related deaths occur among children under five years old. One of the causes of diarrhea is poor access to hygiene and sanitation. Data obtained from the Dungkait Health Center indicate that the village with the lowest sanitation facilities and the highest incidence of diarrhea in children under five is Pangasaan Village. The aim of this study is to describe the hygiene and sanitation conditions related to the incidence of diarrhea in children under five in Pangasaan Village, Tapalang Barat District, Mamuju Regency. Methods: The study design used is cross-sectional. The population in this study includes all households with children under five in Pangasaan Village, totaling 54 households. The sample consists of mothers of children under five, with a total sample size of 54 individuals. The study variables include: drinking water treatment, defecation habits, wastewater management, waste management, and the incidence of diarrhea. Data were collected using questionnaires and observation sheets. The data were analyzed using descriptive analysis. Results: There is no significant relationship between drinking water treatment and the incidence of diarrhea in children under five (p-value = 1). There is also no significant relationship between defecation habits and the incidence of diarrhea in children under five (p-value = 0.176). Similarly, no significant relationship exists between household wastewater management and the incidence of diarrhea in children under five (p-value = 0.575), nor between waste management and the incidence of diarrhea in children under five years old (p-value = 1). Conclusion: Although not statistically significant, toddlers from households with poor sanitation tend to have a higher incidence of diarrhea compared to those from households with better sanitation. Keywords: Diarrhea; Toddlers; Hygiene; Sanitation